Nexus thinking in business: Analysing corporate responses to interconnected global sustainability challenges. Issue 107 (May 2020) - Dahlmann, Frederik; Bullock, Graham
Highlights: Researchers call for nexus thinking beyond energy-food-water policy considerations. Business plays an underexamined role in interconnected sustainability challenges. Companies' responses to nexus challenges are studied using different secondary data. Businesses rely on silo-based approaches but also adopt early forms of nexus thinking. We contribute to wider discussions on the importance of nexus approaches. Abstract: Nexus thinking represents a novel approach to managing sustainability challenges, but little is known about how and to what extent it is being employed by companies. By examining documents from 14 companies identified as "comprehensive-disclosers, " this paper reveals important insights into corporate responses to multiple, interconnected sustainability issues or "nexus challenges". Using qualitative content analysis of companies' responses to the CDP (formerly, Carbon Disclosure Project) climate change, water, forests and supply chain surveys as well as their sustainability reports, we find that while companies largely continue with silo-based approaches to addressing sustainable development challenges, some are beginning to employ more integrated approaches suggestive of embryonic "nexus thinking." Our research provides the first empirical evidence of its kind and contributes to broader debates on the utility of the nexus concept in corporate environmental governance and policymaking.